Profesionalisme Guru Pendidikan Agama Kristen dalam Pengelolaan Kelas - Agus Prihanto; Yuli Pheanto (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The professionalism of Christian Religious Education teachers is an essential part of the educational process, especially in terms of managing the class. This study aims to determine whether the professionalism of Christian religious education teachers is significant in managing the class so that the professionalism of a teacher can play a role in managing class. In addition, this article aims to find out how a professional Christian Religious Education teacher can control the class properly. The research method used in this article is the descriptive qualitative method. The data source is obtained through secondary data sources and presented descriptively. The results of the analysis of this article are that the professionalism of Christian Religious Education teachers is indispensable in classroom management. Professional teachers can utilize every available resource to manage the class well. The resources used to manage the class include 1) Physical resources in the form of classroom furniture and students; 2) Personal resources including the character, intelligence, and spirituality of students; 3) Social environment resources, namely class rules/school rules, culture, and social environment.  AbstrakProfesionalisme guru Pendidikan Agama Kristen merupakan bagian yang penting dalam proses mendidik, khususnya dalam hal mengelolah kelas. Penelitian ini bertujuan untuk mengetahui apakah profesionalisme guru pendidikan agama kristen penting dalam mengelolah kelas, sehingga keprofesionalisme seorang guru tersebut dapat berperan dalam mengelolah kelas. Selain itu artikel ini bertujuan untuk mengetahui bagai mana cara seorang guru Pendidikan Agama Kristen yang profesional dapat mengelolah kelas dengan benar. Metode penelitian yang digunakan pada artikel ini adalah metode kualitatif  deskriptif, sumber data diperoleh melalui sumber data skunder, dan disajikan secara deskriptif. Hasil analisis dari artikel ini adalah profesionalisme guru Pendidikan Agama Kristen sangat dibutuhkan dalam pengelolaan kelas. Guru yang profesional dapat memanfaatkan setiap sumber daya yang ada untuk mengelola kelas dengan baik. Sumber daya yang digunakan untuk mengelola kelas antara lain 1) Sumber daya fisik berupa perabot kelas dan juga peserta didik; 2) Sumber daya personal antara lain karakter, kecerdasan dan kerohanian dari peserta didik; 3) Sumber daya lingkungan sosial yaitu aturan-aturan kelas/ tata tertib sekolah, budaya dan lingkungan sosial.